Investigation of the antitumor effects of anti-inflammatory desloratadine and trimebutine on different types of human cancer cells: An in vitro study - Ozkaya, Semiha Nur; Keskin, Tuba; Tekin, Cigdem; Tekin, Suat; Beytur, Ali (Annals of Medical Research, 2023)
Aim: Inflammation is a process associated with the development and progression of cancer. Desloratadine (DES) and Trimebutin (TMB) are anti-inflammatory agents used in the treatment of various diseases. This study aimed to investigate the antitumor effects of DES and TMB, which exhibit anti-inflammatory effects, on different human cancer cell lines. Materials and Methods: In this study, human prostate (LNCaP), ovarian (A2780), breast (MCF-7) and colon cancer (Caco-2) cell lines were treated with DES and TMB at concentrations of 1, 5, 25, 50 and 100 µM. Cells were treated with the compounds for 6, 12, and 24 hours, and the change in cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The inhibitory concentration 50 (LogIC50) values of the compounds were calculated using GraphPad Prism 8 software based on cell viability results. The genotoxic effects of the compounds on cells were determined using the comet assay. Group comparisons were performed using the Kruskal-Wallis H test and p<0.05 was considered significant. Results: Exposure of LNCaP, A2780, MCF-7, and Caco-2 cells to DES and TMB agents for 6, 12 and 24 hours significantly reduced cell viability (p<0.05). According to the comet assay results, DES and TMB caused significant DNA damage in the cell lines (p<0.05). Conclusion: The study results demonstrate that DES and TMB, which have anti-inflammatory effects, exert cytotoxic effects by inducing DNA damage in cancer cells.